Pengaruh Conformity Consumption Behavior dan Atribut Produk Terhadap Keputusan Pembelian Produk Fashion Pakaian Wanita Merek Colorbox (Studi Pada Generasi Z di Kota Medan): Penelitian - Loisa Theresia Hutagalung; Nicholas Marpaung (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the influence of conformity consumption behavior and product attributes on the purchasing decisions of Generation Z in Medan City regarding Colorbox brand women's fashion apparel. This study uses a quantitative method with an associative approach. The population of this study consisted of 100 respondents determined through purposive sampling. Primary data were collected through a questionnaire. The analysis techniques used include validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results of the study indicate that the variables of conformity consumption behavior and product attributes have a significant influence, both partially and simultaneously, on purchasing decisions. The coefficient of determination test yielded an R value of 0.670, indicating a fairly strong relationship between conformity consumption behavior, product attributes, and purchasing decisions with an R value of 0.670. These findings suggest that social factors and product attributes are important determinants in shaping Generation Z's fashion purchasing decisions, particularly regarding the Colorbox brand.